Meter and Word Setting: Revising Machaut's Monophonic Virelais - Maw, David (Current Musicology, 2002)
Monophonic virelais constitute a significant proportion of Guillaume de Machaut's compositions in the formes fixes; together with the complainte and chanson roial of the Remede de Fortune and the lais, they represent the zenith of a medium which has not since been pursued with either such creative variety or such compositional resource. At first glance, the virelais seem simple, naIve even. Yet closer analytical attention has revealed that they harbor a range of sophistications, whether a subtle interplay of melodic phrase and poetic line,! or a variety of different tonal procedures and motivic reworkings.2 This is no surprise given the remarkable technical skill and creative imagination of Machaut's other compositions. But it is a timely reminder that the monophonic songs are an integral part of his lyric output, rather than a marginal curiosity betraying indebtedness to the trouvere tradition at a time when the lyric genres were focused on the development of polyphony.